Pelatihan Pembuatan Gula Semut Aren dan Jahe Instan di Desa Botosari, Paninggaran, Pekalongan - Achmad Mujib; Aji Hermawan; Sugeng Hari Suseno; Danang Aria Nugroho; Prayoga Suryadarma (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Palm sugar is one of the sweateners which is commonly found in Indonesia. People of Gunung Surat, Botosari Village, Paninggaran, Pekalongan Regency have traditionally produced palm sugar, but the palm sugar is still low quality and sold in bulk. This condition makes the selling value of palm sugar to be low. The aim of the training on making palm sugar and instan ginger beverage was to provide knowledge for the public about the diversification of palm sugar products with high selling value. The implementation of this training was to deliver material and practice of making products. The results of this training was the people of Gunung Surat, Botosari Village, especially members of the palm sugar IKM, know the process of making palm sugar and instant ginger beverage. Through making diversification of palm sugar products, it is expected to be able to increase the income and welfare of the local community.